In-situ formation Ti-Al-C compounds reinforced SiCp/2A14 Al joint: Microstructure evolution and mechanical properties. (June 2022) - Zhang, Mingyang; Wang, Chunming; Mi, Gaoyang; Jiang, Ping; Zhang, Xiong
Highlights: SiCp /2A14 Al joints were prepared via ultra-narrow uniform gap powder feeding assisted laser welding. In-situ formation of TiC and TiAl3 strengthened the fusion zone. The fracture location of the welding joint was in the SiC aggregation area. Abstract: SiCp/2xxx Al matrix composites have been widely used in the aerospace structural components. In order to promote the further application of high-performance welded structures of SiCp/2xxx Al alloys in aerospace field, a Ti powder assisted laser welding strategy was proposed in this study. The strategy of penetration powder feeding laser welding was successfully realized by the clever use of gap coupling spot diameter. The microstructure and mechanical properties of the SiCp/2A14Al welded joints were characterized in detail. Results showed that the regular octahedral TiC and irregular TiAl3 intermetallic formed in-situ were dispersed in the Al matrix. It can been seen from fracture morphology images that the location leading to the final fracture of the SiCp/2A14Al welded joint was the SiC enrichment zone between the fusion zone and the heat affected zone. In addition, the potential technology and design mechanism of powder feeding laser welding SiCp/2A14Al composites were prospectively discussed. This study provides a more detailed view of the phenomenology of gap coupling powder laser welding, adding to our evolving understanding of its welding properties.